2021
DOI: 10.1038/s41598-021-81462-7
|View full text |Cite|
|
Sign up to set email alerts
|

Catechin and curcumin interact with S protein of SARS-CoV2 and ACE2 of human cell membrane: insights from computational studies

Abstract: The recent outbreak of the coronavirus (SARS-CoV2) is an unprecedented threat to human health and society across the globe. In this context, development of suitable interventions is the need of the hour. The viral spike protein (S Protein) and the cognate host cell receptor ACE2 can be considered as effective and appropriate targets for interventions. It is evident from the present computational study, that catechin and curcumin, not only exhibit strong binding affinity to viral S Protein and host receptor ACE… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
117
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(123 citation statements)
references
References 36 publications
1
117
0
5
Order By: Relevance
“…Therefore, MD simulations prove to be effective in studying atomic level interactions and establishing the ligand selectivity towards the target. 8-HDS possesses the capability to fluctuate the RBD site of S protein, which interacts with ACE2 receptor of human cell for the viral infection [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, MD simulations prove to be effective in studying atomic level interactions and establishing the ligand selectivity towards the target. 8-HDS possesses the capability to fluctuate the RBD site of S protein, which interacts with ACE2 receptor of human cell for the viral infection [20].…”
Section: Discussionmentioning
confidence: 99%
“…The entry of SARS-CoV-2 into host cells is mediated through the binding of glycoproteinous spike protein of the virus, the S protein and host cell membrane receptor, i.e. Angiotensin Converting Enzyme 2 (ACE2) [20] (Fig. S1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another in silico approach also revealed that curcumin and catechin were used as potential antiviral polyphenols through the dual inhibition of host cell receptors to the virus (mediated by ACE2) and viral protein entry (S-protein). It should be mentioned that the binding affinity of catechin was more than that of curcumin [ 243 ].…”
Section: Importance Of Phytochemicals In Combating Covid-19mentioning
confidence: 99%
“…Catechins from green tea bind to S1 domain of the spike protein and block its interaction with ACE2 receptor, thus preventing the viral infection. Another study suggests that catechins bind to the amino acids near the receptor binding domain (RBD) of the spike protein and cause fluctuations of alpha helices and beta strands of the RBD-ACE2 complex, thereby hindering the formation of the RBD-ACE2 complex [ 32 ].…”
Section: Introductionmentioning
confidence: 99%